Labour productivity management model taking into account organizational culture of enterprise - A. O. Ivanov (Управление)
Slowdown in global economic growth and in productivity growth complicates socio-economic development of Russia and other countries. Raising income inequalities and their continued stagnation lead to an increase in economic, social, and political tensions in society. Automation and robotization of production processes stimulate uncertainty increase in the labour market. Labour productivity improvement at both micro- and macroeconomic levels is the factor of intensive economic growth, which is caused by the improvement of  efficiency of use of available resources. Results of the implementation of the Russian national project “Labour  productivity and employment support” show that the key part of successful innovations is related to the transformation of organizational culture of enterprise. Specifically, through reorganization of working space of employees and their working hours, reduction in the share of “unnecessary” actions and movements of workers, improvement of self-organization skills, and focus on long-term development.The article concludes that labour productivity management includes management of organizational culture of enterprise. Labour productivity management model has been presented, consisting of three phases: diagnostics, development, and implementation. Each phase involves a sequence of actions, gradually leading to its realization. The model is cyclic and can be repeated unlimited number of times. Use of the model allows you to structure the process of labour productivity improvement, determine the optimal set of resources for its realization, monitor its realization, and make timely adjustments. Specification of system elements of the model has been presented,  including: goal, functions, principles of effective functioning of the model, informational support, human resources  and organizational structure, methods and tools. The criteria for the following results of using the model: effective, limitedly effective, and ineffective have been defined. The model for use to enterprises of any scale and specification that intend to make organizational changes in order to improve labour productivity has been  recommended.